2001
DOI: 10.1614/0890-037x(2001)015[0647:wbprtp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Weed Biomass Production Response to Plant Spacing and Corn (Zea mays) Hybrids Differing in Canopy Architecture1

Abstract: Field experiments were conducted in 1996, 1997, and 1998 at Ste. Anne de Bellevue, Quebec, Canada, and in 1996 at Ottawa, Ontario, Canada, to quantify the impact of corn hybrids, differing in canopy architecture and plant spacing (plant population density and row spacing), on biomass production by transplanted and naturally occurring weeds. The treatments consisted of a factorial combination of corn type (leafy reduced stature [LRS], late-maturing big leaf [LMBL], a conventional Pioneer 3979 [P3979], and, as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 20 publications
3
26
0
4
Order By: Relevance
“…These results agree with Forcella et al (1992), Teasdale (1995), Murphy et al (1996) and Begna et al (2001). However, the interception obtained in the narrow row arrangement was higher than that reported by Murphy et al (1996) and Begna et al (2001); Bullock et al (1988); Teasdale (1995); Barbieri et al (2000) and Andrade et al (2002) reported that the greater PAR interception in narrow rows at flowering was obtained when corn growth at early stages was most limited. Barbieri et al (2000) showed that relative grain yield responses to narrow rows decreased as crop PAR intercepted at flowering with increased wide row arrangement.…”
Section: Ppfd Interceptionsupporting
confidence: 88%
See 2 more Smart Citations
“…These results agree with Forcella et al (1992), Teasdale (1995), Murphy et al (1996) and Begna et al (2001). However, the interception obtained in the narrow row arrangement was higher than that reported by Murphy et al (1996) and Begna et al (2001); Bullock et al (1988); Teasdale (1995); Barbieri et al (2000) and Andrade et al (2002) reported that the greater PAR interception in narrow rows at flowering was obtained when corn growth at early stages was most limited. Barbieri et al (2000) showed that relative grain yield responses to narrow rows decreased as crop PAR intercepted at flowering with increased wide row arrangement.…”
Section: Ppfd Interceptionsupporting
confidence: 88%
“…Murphy et al (1996) showed that corn planted at 50-cm rows intercepted about 8% more photosynthetically active radiation (PAR) at silking than crop at conventional rows, reducing biomass of late-emerging weeds. Similar results were obtained by Begna et al (2001) in corn planted in 38-cm rows. Weed control in corn planted at 5.1 pl m -2 in 76 cm rows and at 9.8 pl m -2 in 38 cm rows where herbicide was either applied at full or one quart of the rates, the suppressive ability of weed at narrow row and high population was related to the increasing amount of light intercepted by the crop (Teasdale, 1995).…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Increased planting densities result in increased green ear yield (Silva et al, 2007) and corn grain yield (Widd icombe & Thelen, 2002). On the other hand, weed management is facilitated as row spacing values are reduced in corn seeding, with the goal of achieving agricultural sustainability (Balbinot Junior & Fleck, 2004;Begna et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…A interceptação de radiação pela cultura do milho pode ser aumentada pelo uso de espaçamentos mais estreitos entre linhas e densidades mais elevadas (Begna et al, 2001). Isso resulta em redução da disponibilidade de radiação solar para a porção inferior do dossel.…”
Section: Introductionunclassified